Children’s Narrative Elaboration After Reading a Storybook Versus Viewing a Video - Crawshaw, Camilla E.; Kern, Friederike; Mertens, Ulrich; Rohlfing, Katharina J. (Frontiers in Psychology, 2020)
Previous studies have found that narrative input conveyed through different media influences the structure and content of children's narrative retellings. Visual, televised narratives appear to elicit richer and more detailed narratives than traditional, orally transmitted storybook media. To extend this prior work and drawing from research on narrative elaboration, the current study's main goal was to identify the core plot component differences (the who, what, where, when, why, and how of a story) between children's retellings of televised versus traditional storybook narratives. However, because children also differ individually in their IQ, we further incorporated this variable into our analysis of children’s narrative retellings. For our purpose, a novel coding schema was developed, following and extending the existing narrative elaboration approaches. Participants were 46 typically developing children aged 4–5 years from Germany. The current study incorporated two narrative input conditions to which children were randomly assigned: in the video condition, children watched a nonverbal, visually conveyed, televised story from a DVD; and in the book condition, children read the story with an adult and experienced an orally conveyed version in the form of a book with minimal accompanying pictures. In both conditions, the same story was conveyed. After including IQ as a covariate in our analyses, results show that the children from the video condition gave significantly more elaborated retellings, particularly across the who, what, and where (sub-)components. Differences between the conditions in the component when, how and why did not reach statistical significance. Our findings indicate that different media types entail differential cognitive processing demands of a story, resulting in type-specific memories and narratives. The effect of different medial conditions was significant and persisted when individual differences in cognitive development were considered. Consequences for children's development, education, and interaction with and within today's digital world are discussed.